Assholes : a theory - James, Aaron, (Aaron J.) (Toronto, Canada : Doubleday, 2012)
A philosophy professor describes the elements that can combine to make someone behave in an unbelievably disturbing and stress-causing manner and offers practical concepts to help develop constructive ways of dealing with these people and the problems they pose.
A theory -- Naming names -- Newer asshole styles -- Gender, nature, blame -- Asshole management -- Asshole capitalism -- Accepting the given -- Coda: letter to an asshole.
Includes bibliographical references and index.
Koleksi sumbangan Tun Ahmad Sarji Abdul Hamid
Keywords: Egoism; Conduct of life